(untitled) (Research, Society and Development, 2021)
This study discusses the materiality circulating in the Gentil Bittencourt Institute, in Belém do Pará, in the beginning of the 20th century, a period in which the city experienced great transformations and conflicts promoted by the aspirations of a civilizing project of a society that used education as an ideological tool in its practical, scientific and political dimensions. Thus, we strive to investigate education in the state of Pará, analyzing objects and artifacts in the field of school material culture from the premises of the Gentil Bitencourt Institute. We aim, therefore, to analyze the presence of objects, artifacts, architecture and practices contained in the organization of everyday school life in the aforementioned institute, considering the time of its inauguration, in 1906 in the city of Belém do Pará. Methodologically, we used two moments: first, the carrying out an exploratory study allowing to identify the sources in the Museum of the Instituto Gentil Bittencourt, as well as in its library; later, we present a brief theoretical articulation. Thus, taking as an object of investigation the school materiality of the Gentil Bitencourt Institute, we have the following issue: how is school material culture configured in the school space with its school practices and artifacts? The analyzes carried out for the development of this object allowed us to perceive how the historical, cultural and social development of the state of Pará interfered with the materiality of the educational scenario. We also found that the use and arrangement of objects and artifacts displayed in the structure of the analyzed school building, as well as school practices, reveal the organization of classes and the moral, civic and scientific training, focused on the pedagogical precepts established in the regulations of public education in Pará, in the mid-twentieth century.